Penyebab Mahasiswa Penerima KIP-K Tidak Berprestasi Akademik di Universitas Jember - Khoirul Anam; Arif Arif; Sari Dewi Poerwanti (Jurnal Multidisiplin Ibrahimy, 2025)
It is recorded that 6,730 students at the University of Jember are recipients of the KIP-K, but only 78 students have achieved academic excellence. This means that less than 2% of KIP-K recipient students have been able to achieve academic success at the University of Jember. This contrasts with the specific characteristics of KIP-K recipient students, who are economically disadvantaged but have good academic potential. Therefore, it is important to conduct research on the reasons why KIP-K recipient students do not achieve academic success at the University of Jember from the perspective of Social Welfare Science. The aim of this research is to identify, describe, and analyze the causes of KIP-K recipient students' lack of academic achievement at the University of Jember. This study uses a qualitative approach with a descriptive type. The results of the study indicate that there are two main causes for KIP-K recipient students' lack of academic achievement at the University of Jember, namely internal and external causes. Internal causes include suboptimal personal development efforts by the students and low motivation to achieve academic excellence, while external causes include a weak academic culture, limited platforms for students to excel academically, and the absence of mandatory requirements to achieve academic excellence at the University of Jember. From these findings, it can be concluded that the suboptimal personal development, coupled with the weak academic culture at the University of Jember, are the primary reasons why KIP-K recipient students do not achieve academic success at the University of Jember.